Концептуальні засади гнучкого менеджменту змін у контексті забезпечення сталого розвитку підприємств - Підгірна, В.Н.; Пушак, Я.Я.; Зибарева, О.В. (Вісник економічної науки України, 2025)
Сформульовано проблему необхідності інтеграції гнучкого менеджменту змін у систему забезпечення сталого розвитку підприємств в умовах глобальної невизначеності та цифровізації економіки. Обґрунтовано, що адаптивність, швидкість реагування та орієнтація на цінності ESG (екологічні, соціальні та управлінські принципи) є ключовими чинниками стійкості бізнесу. Запропоновано концептуальне поєднання моделей Agile, Lean і Kaizen як основи для створення адаптивно-сталих підприємств, здатних ефективно функціонувати у VUCA/BANI-середовищі. Розкрито взаємозв’язок між управлінням змінами та сталим розвитком, визначено роль гнучкого лідерства й моделі кругової економіки у формуванні стратегії довгострокової конкурентоспроможності. The article substantiates the relevance of integrating flexible change management into the system of sustainable enterprise development in the context of global uncertainty, technological turbulence, and digital transformation of the economy. The study emphasizes that in the modern VUCA/BANI environment, where volatility, uncertainty, complexity, and ambiguity dominate, the ability of organizations to adapt quickly and make informed decisions becomes a decisive factor for their survival and long-term growth. It is proved that adaptability, rapid response, teamwork, and adherence to ESG (Environmental, Social, and Governance) principles are the key determinants of business resilience and strategic stability. The authors propose a conceptual synthesis of Agile, Lean, and Kaizen methodologies as a foundation for forming adaptive and sustainable enterprises. This approach enables the combination of innovation and flexibility with social responsibility and environmental consciousness. It is noted that effective transformation requires not only procedural and technological renewal but also responsible leadership and the implementation of the circular economy model aimed at resource efficiency and ecological balance. The research demonstrates that flexible change management acts both as a mechanism and a catalyst for achieving sustainable development in the digital economy. It ensures a dynamic balance between economic efficiency, social justice, and environmental safety, thus creating a modern management paradigm that integrates innovation, resilience, ethics, and sustainability. The conceptual model presented contributes to strengthening the competitive position of enterprises, improving their ability to recover from crises, and ensuring their long-term development in a constantly changing global environment.